PROFILE OF HISTORY OF FEBRILE SEIZURE IN PATIENTS WITH EPILEPSY - Rayhan Muhammad Basyarahil; Wardah Rahmatul Islamiyah; Prastiya Indra Gunawan (Malang Neurology Journal, 2021)
Background: Febrile seizure is convulsions with fever (temperature ³38°C) with no central nervous system infection that commonly found in children (6-60 months). Febrile seizures do not always mean the child has epilepsy. However, febrile seizures can be a possible long-term risk factor for epilepsy.